CD1d-Invariant Natural Killer T Cell-Based Cancer Immunotherapy: α-Galactosylceramide and Beyond - King, Lisa A.; Lameris, Roeland; de Gruijl, Tanja D.; van der Vliet, Hans J. (Frontiers in Immunology, 2018)
CD1d-restricted invariant natural killer T (iNKT) cells are considered an attractive target for cancer immunotherapy. Upon their activation by glycolipid antigen and/or cytokines, iNKT cells can induce direct lysis of tumor cells but can also induce antitumor immune response via their rapid production of proinflammatory cytokines that trigger the cytotoxic machinery of other components of the innate and adaptive immune system. Here, we provide an overview of various therapeutic approaches that have been evaluated or that are currently being developed and/or explored. These include administration of α-GalCer or alternative (glyco) lipid antigens, glycolipid loaded antigen-presenting cells (APCs) and liposomes, strategies that enhance CD1d expression levels or are based on ligation of CD1d, adoptive transfer of iNKT cells or CAR iNKT cells, and tumor targeting of iNKT cells.